SCHOOL PRINCIPAL MANAGEMENT IN REALIZING FREEDOM FOR DIGITALIZED LEARNING IN PRIMARY SCHOOLS - Syofian, Syofan; Yani T, Ahmad (PROGRES PENDIDIKAN, 2024)
This research examines the leadership management of elementary school principals in their efforts to realize Freedom of Learning in the Era of Digitalization. The aim of this research is to describe and analyze the leadership management of the principal in realizing the Freedom of Learning era of digitalization in Elementary Schools. The research method used is qualitative research with descriptive explanation. Research sources include books, journals, websites and magazines. The results of the research show that the Merdeka Belajar curriculum launched by the government, the integration of the two aims to prepare a better generation for the nation. To make this happen requires cooperation from various parties, especially in the school environment, namely through the role of the school principal. The impact of this research is that the principal's leadership management in the era of digitalization is able to develop the vision, mission and goals of the school through the aspect of a visionary leader, creating a digital era learning culture that is able to meet students' needs, is able to improve a condition or problem systematically, is superior in professional practice to able to create a conducive environment for learning and working in this era of digitalization. By fulfilling these five aspects, the school principal's leadership management will be able to be created well so that a synergistic relationship between components in the school will be realized.